Validation of the Model on the Impact of Leader's Cultural Intelligence on Organizational Performance Empowerment Considering the Mediating Role of Organizational Structure - Sarvari, Gholamreza; Razeghi, Saeed; Mahmoudian, Hamid (Management Strategies and Engineering Sciences, 2024)
The aim of the present study is to validate the model of the impact of a leader's cultural intelligence on organizational performance empowerment, considering the mediating role of organizational structure. In the first phase, the research is exploratory in terms of its objective and fundamental in terms of its outcome, utilizing qualitative data. In the second phase, the research is explanatory in terms of its objective and developmental in terms of its outcome, employing quantitative data. In the qualitative phase, the target population consisted of university faculty members and management experts in Khuzestan province. Purposeful sampling was used in the qualitative phase, and through theoretical purposeful sampling, the sample members were identified. The sample size in the qualitative phase was determined based on the level of saturation, with interviews conducted with 20 faculty members and experts in the relevant field. The target population for the quantitative part of the research consisted of professionals and academics specializing in management and cultural studies. The sample size was determined to be 384, with 300 completed questionnaires ultimately received. For data collection in the present study, semi-structured interviews with experts were used to design the questionnaire. Based on the results of the interviews with experts and the indicators and components derived from them, a questionnaire was developed. Data analysis from the interviews was conducted using the grounded theory approach based on Strauss and Corbin's (1998) systematic approach, which includes open, axial, and selective coding stages. The results revealed that the model of the impact of leader's cultural intelligence on organizational performance empowerment, considering the mediating role of organizational structure, has adequate validity.